Comparison of Oxygen Adsorption and Platinum Dissolution in Acid and Alkaline Solutions Using Electrochemical Quartz Crystal Microbalance. Issue 22 (20th October 2022) - Strandberg, Linnéa; Shokhen, Victor; Luneau, Mathilde; Lindbergh, Göran; Lagergren, Carina; Wickman, Björn
Abstract: Platinum (Pt) is a widely used electrocatalyst material in fuel cells and electrolysers. Proton exchange membrane (PEM) fuel cells and electrolysis operate under highly acidic conditions whereas the more recently developed anion exchange membrane (AEM) processes take place under alkaline conditions. Pt dissolution and Pt oxidation during operation and varying potentials has been studied mainly for the acidic PEM and less for the alkaline AEM. This study presents a comparison of Pt dissolution and Pt oxidation in 0.5 M H2 SO4 and 1 M KOH using electrochemical quartz crystal microbalance (EQCM) on Pt thin films. Physical characterisation using electron microscopy and atomic force microscopy (AFM) revealed small, yet significant differences in the Pt film surface structure, which is related to differences in measured electrochemical surface area (ECSA). The mass increase from adsorption of oxygenated species and Pt oxidation is higher in alkaline conditions compared to in acid while dissolution of Pt is similar. Abstract : Electrochemical Quartz Crystal Microbalance/Pt : Dissolution and oxidation of platinum thin films were measured in acidic and alkaline electrolytes with varying potential cycling ranges using electrochemical quartz crystal microbalance.